2021
DOI: 10.1155/2021/9140602
|View full text |Cite
|
Sign up to set email alerts
|

Treg/Th17 Cell Balance in Patients with Hepatitis B Virus‐Related Acute‐on‐Chronic Liver Failure at Different Disease Stages

Abstract: Background. T-helper 17 (Th17) and CD4+CD25+ T-regulatory (Treg) cells play important roles in the pathogenesis of hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF). This study is aimed at investigating shifts in Treg/Th17 balance in the peripheral blood of HBV-ACLF patients at different disease stages. Methods. Sixty HBV-ACLF patients, admitted to the First Hospital of Hunan University of Chinese Medicine, China, including early-stage ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Treg and Th17 cells are CD4+ T cells different from classical Th1 and Th2 cells. Treg cells mainly secrete IL-10 and TGF- β 1, which improve hepatocyte inflammation by regulating other immune cell functions and thus controlling the body's immune response, while Th17 cells mainly secrete inflammatory factors such as IL-17 and IL-22 and induce proinflammatory factors such as IL-6 and TNF- α , both of which antagonize each other in function and differentiation [ 20 ]. We can also fully confirm this after testing the inflammatory factors and OS responses in NAFLD patients and healthy persons.…”
Section: Discussionmentioning
confidence: 99%
“…Treg and Th17 cells are CD4+ T cells different from classical Th1 and Th2 cells. Treg cells mainly secrete IL-10 and TGF- β 1, which improve hepatocyte inflammation by regulating other immune cell functions and thus controlling the body's immune response, while Th17 cells mainly secrete inflammatory factors such as IL-17 and IL-22 and induce proinflammatory factors such as IL-6 and TNF- α , both of which antagonize each other in function and differentiation [ 20 ]. We can also fully confirm this after testing the inflammatory factors and OS responses in NAFLD patients and healthy persons.…”
Section: Discussionmentioning
confidence: 99%
“…CC chemokine ligand 20, a chemotactic protein secreted by hepatocytes, is expressed in liver tissues, facilitating the development of inflammatory responses in liver tissues (22,23). Moreover, Treg/Th17 cytokines are important players in immuno-inflammatory regulation (24). The changes in the levels of Treg/Th17 cytokines (TGF-β, IL-10, IL-23, and TNF-α) are closely related to the Treg/Th17 balance.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Additionally, previous studies demonstrated CD4+CD25+ T-regulatory cells were independent risk factors for patients with ACLF. 21 , 22 …”
Section: Discussionmentioning
confidence: 99%